2021
DOI: 10.1177/10556656211036607
|View full text |Cite
|
Sign up to set email alerts
|

Anterior “W” Tongue Reduction for Macroglossia in Beckwith-Wiedemann Syndrome

Abstract: Introduction Macroglossia occurs in 80% to 99% of patients with Beckwith-Wiedemann syndrome (BWS) and a variety of surgical techniques for tongue reduction are offered by surgeons. The purpose of this study is to evaluate the postoperative outcomes of the anterior “W” tongue reduction technique in patients with BWS. Methods A retrospective review was conducted of all patients diagnosed with BWS that underwent an anterior “W” tongue reduction for macroglossia in the past 7 years, performed by 2 surgeons. Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Most experts do not recommend operating glossectomy surgery in <6 months, while a minority of researchers authorized. [24][25][26] The concern of those experts who oppose operating at an early age is, that considering the development of tongue and oral cavity are dynamic growth processes, the oral cavity may accommodate the tongue with the growth of children. In our cohort study, the average age at the time of surgery is 14.05 months, which is within the age range recommended by most experts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most experts do not recommend operating glossectomy surgery in <6 months, while a minority of researchers authorized. [24][25][26] The concern of those experts who oppose operating at an early age is, that considering the development of tongue and oral cavity are dynamic growth processes, the oral cavity may accommodate the tongue with the growth of children. In our cohort study, the average age at the time of surgery is 14.05 months, which is within the age range recommended by most experts.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of severity in macroglossia patients challenges standardized treatment. Most experts do not recommend operating glossectomy surgery in <6 months, while a minority of researchers authorized 24–26. The concern of those experts who oppose operating at an early age is, that considering the development of tongue and oral cavity are dynamic growth processes, the oral cavity may accommodate the tongue with the growth of children.…”
Section: Discussionmentioning
confidence: 99%
“…Já o excesso de peso ao nascer é característica secundária, atribuindo 1 ponto no diagnóstico clínico, mas que também apresenta prevalência expressiva em neonatos com a síndrome, de aproximadamente 75%, esse dado é evidenciado em coorte realizada na china com 26.082 neonatos, dos quais 16 possuíam BWp. 3,9,10 O heredograma das famílias dos 2 pacientes se encaixa na grande taxa da afirmação da ocorrência da doença de forma esporádica, que representa 85% dos casos, enquanto 15% exibem herança familiar. Entretanto, aproximadamente 20% dos pacientes portadores de hipermetilação em IC1 podem apresentar pequenas variações do número de cópias (CNVs) do conteúdo genômico, fator associado ao maior risco de recorrência da alteração molecular associada ao BWp, aumentando o risco para 50% se houver herança do alelo materno.…”
Section: Ambosunclassified
“…Various tongue reduction techniques have been conducted in craniofacial centers, each with distinct incision patterns and methods, including keyhole, stellate, anterior wedge, and modified W-shaped patterns. For example, Ainuz et al [ 8 ] reported that patients who underwent surgery using the anterior “W” tongue reduction technique had low rates of perioperative complications and showed significant improvements in oral competence.…”
Section: Introductionmentioning
confidence: 99%